EFFECT OF PEPPERMINT OIL ON THE QUALITATIVE PROPERTIES OF SOME PROCESSED MEAT PRODUCTS: EFFECT OF PEPPERMINT OIL ON THE QUALITATIVE PROPERTIES OF SOME PROCESSED MEAT PRODUCTS (Iraqi Journal of Market Research and Consumer Protection, 2026)
The current study aimed to evaluate the qualitative, chemical, and sensory aspects of processed meat products (camel meat burgers) preserved through refrigeration at 4°C +2 for 12 d. It was treated with three concentrations of peppermint oil extract. The volatile oils from peppermint leaves were extracted using steam distillation with a Clevenger apparatus. The study involved adding three concentrations of peppermint oil (0.6%, 0.8%, and 1%) to the camel meat burgers manufactured according to the Iraqi Standard Specifications for the year 2019, No. 5110, and conducting chemical, qualitative Protein, Lipid, Ash, Moisture, CHO, PH, PV (m.equ/kg), T.B.A (mg MDA/kg), T.V.N (mg/100gm), FFA, and sensory tests over 1, 4, 8, and 12 d of refrigerated storage. We conclude from this study that peppermint oil can be used to prolong the shelf life of camel meat burgers by refrigeration for up to 12 d and to maintain the chemical and qualitative characteristics of camel meat burgers within acceptable limits from the beginning of treatment without the appearance of unacceptable flavors, tastes and textures.